Getting Past the Sticking Points: A Questioning Framework for Fraction Multiplication - Johanning, Debra (Ohio Journal of School Mathematics, 2019)
While the procedure for multiplying a fraction times a fraction may seem straightforward, understanding why the procedure works is complex. Ohio’s New Learning Standards for mathematics identify the need to use visual models and story contexts to develop student understanding of fraction multiplication. This article outlines a questioning framework that, when used with visual models and story contexts, can help students with four common fraction × fraction ”sticking” points.